The impact of cultural values, emotional intelligence, social responsibility, and perceived social norms on helping behavior in Malaysian young adults - Ma’rof, Aini Azeqa; Dahamat Azam, Mohamad Naqiuddin; Rosnon, Mohd Roslan (Human Resource Management Academic Research Society, 2024)
This study investigates the influence of cultural values, emotional intelligence, social responsibility, and perceived social norms on helping behavior among Malaysian young adults. Using a sample of 415 participants, data were analyzed through correlation and multiple regression methods. The results indicate that social responsibility (β = 0.44, p < .001) was the strongest predictor of helping behavior, followed by perceived social norms (β = 0.39, p < .001), emotional intelligence (β = 0.36, p < .001), and cultural values (β = 0.24, p = .002). Together, these predictors accounted for 69.3% of the variance in helping behavior (R² = 0.693, F(4, 410) = 213.45, p < .001). These findings highlight the pivotal roles of moral obligation, societal expectations, and emotional awareness in fostering prosocial actions within a collectivist cultural context. The study provides key insights for designing community and educational programs aimed at promoting helping behavior among youth.